Money and Inflation at the Time of Covid - Tim Congdon (Edward Elgar Publishing, 2025)
How is the inflation flare-up of the early 2020s to be explained? In this book Tim Congdon, one of the world's leading monetary analysts, argues that a money growth explosion in spring and summer 2020 was the main cause. The book is scholarly, but also lively and readable. Congdon restates the quantity theory of money, advocating the usefulness of a broadly-defined measure of money which includes all, or nearly all, bank deposits. He applies this theory to the macroeconomic events of the early 2020s, and debunks the widespread view that inflation was caused by unforeseeable supply-side shocks. In spring 2020 Congdon was almost unique in forecasting the inflation flare-up. His position contrasted sharply with the overwhelming majority of economists who instead believed that Covid-19 would lead to several years of disinflation. Congdon was right and nearly all of his profession was wrong. Congdon is very critical of leading central banks, particularly the USA's Federal Reserve. Money and Inflation at the Time of Covid is a brilliant challenge to conventional macroeconomic thinking. It provides vital insights into recent events for students and academics in economics and finance, as well as economists, policymakers and other practitioners working in financial institutions, companies and consultancies.
Keywords: 330; Quantity Theory Of Money; Monetarism; Macroeconomic Forecasting; Central Banks; Federal Reserve; John Mayndard Keynes; Milton Friedman